Dilema Pengalaman Informasi: Analisis Konseptual - Kamil, Rusdan; Laksmi, Laksmi (UI Scholars Hub, 2023)
The information experience domain is a field of human information behavior research, concerned with one's engagement with sensory information using personal cognitive and affective experiences. The development of information technology and social media causes a flood of information which results in misinformation, disinformation, fake news, and hate speech in the public information space which increases personal distraction, this is also known as the phenomenon of information pathology. Another type of information pathology is the phenomenon of tensions in behavior and information practices presented as information experience dilemmas. This study aims to define, understand, and explain various forms of information experience dilemmas, there is a concept of tension that appears in various contexts. Case studies in the context of the global Covid-19 pandemic are presented to illustrate the operationalization of the definitions and variations of the information experience dilemma. The results of the research contribute to the field of information experience research that has been developed by taking the perspective of distraction in the public information space and helping to understand how to design library service systems and information systems that address affective and cognitive tensions in the disinformation era.